ANALISIS EKONOMI RUMAH TANGGA PETANI PADA USAHATANI KAKAO RAKYAT DI KABUPATEN BLITAR - Rena Yunita Rahman; Yuli Hariyati (University of Jember, 2019)
As annual crop farmers, the household of cocoa farmers apply diversification livelihood strategy which depends on the season, the labor market, and the free time of each family member to make ends meet. This particular research was conducted in order to analyze the performance and economic behavior of the cocoa farmer households. The research was located in Udanawu and Bakung district with a sample of 45 cocoa farmer households. In order to answer the purpose of this research,a sequences of analysis through tabulation analysis and simultaneous equation models which then estimated using the Two Stage Least Squares (2SLS) method. The results showed that cocoa farming income is significantly influenced by the cocoa prices, production, the number of productive cocoa plants and costs. The expenditure of food on farmer households is significantly affected by the number of the children of the family who are at the time receiving education in school. The most important thing that can be recommended to increase farmer’s income is cocoa bean should be fermented. There needs to be strengthening of institution therefore, the farmers' bargaining position increases and new government policies to push the issuance of mandatory rules for cocoa fermentation.